Exploring the effects of maize canopy on the spatiotemporal distribution heterogeneity of the determinants of sprinkler irrigation droplet splash erosivity - Zhongrui Zhu; Jiusheng Li; Delan Zhu (Agricultural Water Management)
To fully understand the sprinkler irrigation-crop-soil continuum, prevent sprinkler erosion, and ensure good development of sprinkler technology, it is essential to characterize the spatiotemporal variability of physical parameters and the splash erosion potential of sprinkler water droplets. The influences of maize canopy and sprinkler characteristics on the spatiotemporal distribution patterns of throughfall, droplet physical parameters, and splash erosion potential were investigated using a 2D-Video-Distrometer. The results showed that MC negatively affected throughfall generation. Irrigation characteristics could not fundamentally reverse the influence of MC on the sprinkler water distribution evenness. Compared to the early stages, the large throughfall at the later stages occurred near the stem base. MC reduced the KEV and SER of sprinkler water droplets. Dripping drops generated on maize leaves caused splash erosion. The SDP laws of KEV and SER of throughfall droplets were basically the same. Contrary to others, the DD of throughfall increased concomitant with the application of sprinkler droplets of 1.48 mm. MC positively influenced the CV of the DD of sprinkler water. Changes in the volume proportions of dripping drops and inadequately breaking droplets resulted in the SDP of the DD of throughfall. The percentages of the Veq of throughfall droplets at different growth stages were 86.81 %, 77.06 %, 55.08 %, and 51.48 %, respectively. Only treatments of 1.48 mm increased the Veq of throughfall droplets. MC and DD affected the distribution heterogeneity of the Veq of throughfall droplets. Differences in the Veqs of large droplets were responsible for the SDP of the velocities of throughfall droplets. Only treatments with small droplets significantly reduced the number of throughfall droplets. And the number of throughfall droplets characterized a SDP with greater values the farther from the stem, whereas others were opposite. The results will provide theoretical and applied implications for diversifying the sprinkler-crop-soil continuum and elucidate the involvement of sprinkler irrigation in the hydrogeochemical cycle of agricultural land.